. What is the H.C.F. of


What is the H.C.F. of x3 – x2 – 4x – 6 and x2 – 2x – 3 ?


A. x + 1
B. x – 1
C. x + 3
D. x – 3

 




 

Best Answer

Answer ||| D

Solution |||

Given: x3 – x2 – 4x – 6 and x2 – 2x – 3

To Find: HCF

We have, x3 – x2 – 4x – 6 and x2 – 2x – 3

x2 – 2x – 3

⇒ x2 – 3x + x – 3

⇒ x(x – 3) + 1(x – 3)

⇒ (x + 1)(x – 3) … (i)

Now for, x3 – x2 – 4x – 6

⇒ x3 + 2x2 – 3x2 + 2x – 6x – 6

⇒ x3 + 2x2 + 2x – 3x2 – 6x – 6

⇒ x (x2 + 2x + 2) -3 (x2 + 2x + 2)

⇒ (x – 3) (x2 + 2x + 2) … (ii)

For, x2 + 2x + 2 , D=-4<0 (No further factorization is possible)

Clearly from eqn. (i) and eqn. (ii)

HCF = (x – 3)

Talk to Our counsellor